Correlation of serum Krebs von den Lungen-6 levels with fibrosis score on high resolution chest tomography and pulmonary function parameters in treatment naïve Idiopathic Pulmonary Fibrosis - Sanjan, Ganesh; Sharma, Prakhar; Banerjee, Saikat; Sivaramakrishnan, Prakash; Sherwani, Poonam; Atif Mirza, Anissa; Sindhwani, Girish; Arvind Bahurupi, Yogesh (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2024)
Background: While serum Krebs von den Lungen-6 (KL-6) has been found to be a helpful    biomarker in interstitial lung diseases for evaluating disease severity and progression, especially in connective tissue disease-associated interstitial lung disease (CTD ILD) and idiopathic non-specific interstitial pneumonia (NSIP), data on correlation of serum KL-6 levels with radiological fibrosis and pulmonary function parameters is lacking in treatment naïve Idiopathic Pulmonary Fibrosis (IPF) patients. Methods: Serum KL-6 levels were measured in thirty-nine treatment naïve newly detected IPF patients using automated immunofluorescence enzyme assay (AIA) by Tosoh Corporation, bioscience division, Tokyo, Japan. Fibrosis score was calculated by independent visual assessment of the pattern and severity of abnormalities on high resolution computed tomography (HRCT) thorax. HRCT fibrosis scores were correlated with serum KL-6 levels and pulmonary function parameters like forced vital capacity (FVC), diffusion capacity of lung for carbon monoxide (DLco). Results: Median value of serum KL-6 levels was 1519 U/ml (range 199.41-6055 U/ml). There was positive correlation of serum KL-6 with HRCT fibrosis score (r=0.692, p